Correlation between of hepatitis A virus infection and vitamin B12 level in Iraqi patients - Mustafa Jawad Kadham; Amran M. AL-Erjan; Rawaa Najim Alkhamessi (Zien Journals, 2022)
Hepatitis A is a public health problem all over the world, especially in developing countries, because the virus is so common in the environment. Anti-HAV IgM antibodies were detected in the serum of 100 of the 120 persons (patients group) collected from the Al-Zahra hospital in Al-rusafa/Baghdad between November 2021 and March 2022. Twenty individuals with negative blood levels of anti-HAV IgM antibodies were deemed a control group. Anti-HAV IgM antibodies were significantly higher (P <0.001) in hepatitis A patients than controls using a solid phase, two-step incubation, antibody capture ELISA kit, indicating acute infection. The majority of HAV patients (91% of all patients) were found during the first decade (1-10 years), whereas 9% were found within the second decade (10-20 years). HAV infection is spread evenly across genders in this research. As a result, females and males had no statistically considerable differences, with a ratio of (1 female: 0.786 male) and a proportion of 56% females vs 44% males. The study showed a considerable decrease in vitamin B12 in male patients with HAV (426.09 ± 35.61 pg/mL) comparing with healthy control (566.45 ± 28.06 pg/mL) (P= 0.001). While in females, the findings displayed a considerable decrease in the patient’s group (595.01 ± 47.47 pg/mL) compared with the control group(721.04 ± 58.28 pg/mL)>
Keywords: HAV; hepatitis; vitamin b12; HAV IgM